49th AIAA Aerospace Sciences Meeting Including the New Horizons Forum and Aerospace Exposition 2011
DOI: 10.2514/6.2011-1297
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Detached Eddy Simulation of a Stall Flow Over NACA0012 Airfoil Using High Order Schemes

Abstract: Delayed-Detached Eddy Simulation (DDES) is conducted to simulate aerodynamic stall flow over NACA0012 airfoil at 45 • angle of attack. DDES is an improved version of DES97 to avoid Modeled-Stress Depletion (MSD) in attached boundary layer by redefining the length scale of DES97. The test of DDES for the flat plate shows that the delayed LES function facilitates DDES to preserve eddy viscosity even with a severe grid that makes DES to undergo MSD. For comparison, DES97 and URANS also were conducted for the stal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 19 publications
0
13
0
2
Order By: Relevance
“…Gao et al [21] performed 2.5D LES simulations of the flow field around a single static airfoil and found that the 2D model is not adequate for predicting unsteady flow structures with large-scale separations around airfoils at relatively high AOAs. Furthermore, Travin et al [22], Bertagnolio et al [23], and IM and Zha [24] presented simulations of a single airfoil beyond stall using the DES method, which is essentially a hybrid model of RANS and LES. Results of the 2.5 DES model are clearly superior over those of the 2.5D URANS models.…”
Section: Introductionmentioning
confidence: 99%
“…Gao et al [21] performed 2.5D LES simulations of the flow field around a single static airfoil and found that the 2D model is not adequate for predicting unsteady flow structures with large-scale separations around airfoils at relatively high AOAs. Furthermore, Travin et al [22], Bertagnolio et al [23], and IM and Zha [24] presented simulations of a single airfoil beyond stall using the DES method, which is essentially a hybrid model of RANS and LES. Results of the 2.5 DES model are clearly superior over those of the 2.5D URANS models.…”
Section: Introductionmentioning
confidence: 99%
“…A set of 4th order and 6th order central differencing schemes are devised to match the same stencil width of the WENO schemes for the viscous terms [19,20]. For turbulent simulations, FASIP has implemented Detached Eddy Simulation (DES) [21,22,23,24,25,26,27], Large Eddy Simulation(LES) [20,28], and Reynolds averaged Navier-Stokes (RANS) [29,19,30,31,32,33,34,35]. An implicit 2nd order time accurate scheme with pseudo time and unfactored Gauss-Seidel line relaxation is employed for time marching.…”
Section: Methodsmentioning
confidence: 99%
“…The validation of current DDES methodology for the stalled flow over NACA0012 airfoil at 45 • angle of attack was conducted by the present authors [8]. The DES predicts the drag accurately compared to the experiment, whereas the URANS model overpredicts the drag by about 33%.…”
Section: Delayed Detached Eddy Simulationmentioning
confidence: 98%
“…By using the RANS model near walls, the mesh size as well as the CPU time can be tremendously reduced. It is shown [6,7,8] that the use of hybrid RANS/LES approaches is very effective for the large structure of vortical flow predictions. In [9], DES is used to simulate the spike stall inception of a transonic rotor.…”
Section: Introductionmentioning
confidence: 99%